2023
DOI: 10.1093/ecco-jcc/jjad157
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatobiliary Manifestations in Inflammatory Bowel Disease: A GRADE Assessed Systematic Review and Meta-Analysis of more than 1.7 Million Patients

Alireza Beheshti Maal,
Mohammad Amin Shahrbaf,
Bahareh Sadri
et al.

Abstract: Background and Aims Background: Inflammatory bowel disease (IBD) is an immune-mediated group of chronic gastrointestinal (GI) disorders. Patients with IBD may experience extraintestinal manifestations, such as the hepatobiliary complications. This meta-analysis aims to assess the prevalence of different hepatic manifestations in IBD patients. Methods For this systematic review and meta-analysis, PubMed, Scopus, Web of Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 159 publications
0
3
0
2
Order By: Relevance
“…(2023 г.) в систематическом обзоре с метаанализом данных более чем 1,7 млн пациентов указывают, что у 3,5% пациентов с ВЗК могут наблюдаться печеночные проявления различного характера [69].…”
Section: внекишечные проявленияunclassified
See 1 more Smart Citation
“…(2023 г.) в систематическом обзоре с метаанализом данных более чем 1,7 млн пациентов указывают, что у 3,5% пациентов с ВЗК могут наблюдаться печеночные проявления различного характера [69].…”
Section: внекишечные проявленияunclassified
“…По результатам последних исследований, распространенность неалкогольной жировой болезни печени у пациентов с ВЗК составляет от 21 до 32% [69]. Так, в очень крупном метаанализе M. Zamani и соавт.…”
Section: внекишечные проявленияunclassified
“…It is estimated that up to 26.1% of patients with IBD have concurrent MASLD. Among the patients with MASLD, the prevalence of UC was as high as 41.7% ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of NAFLD in the general population has increased significantly over time, from 25.5% before 2005 to 37.8% in 2016 or later [11]. A recent epidemiologic study investigating the occurrence of hepatobiliary conditions in IBD patients revealed a median 26% prevalence of NAFLD [12,13]. Crucially, patients with IBD exhibit an elevated rate of NAFLD diagnosis independent of traditional metabolic risk factors, such as obesity and diabetes [14].…”
Section: Introductionmentioning
confidence: 99%